2020
DOI: 10.2174/1573411016999200715162006
|View full text |Cite
|
Sign up to set email alerts
|

Melia azedarach Activated Carbon and its novel TiO2 Nanocomposite for Chemisorption and Photodecoloration of Reactive Orange 16: Isotherm and Kinetic Modeling

Abstract: Background: Bulk generated textile wastewater loaded with dyes is posing stern threat to aquatic health especially when dumped without prior treatment. Lignocellulosic waste based activated carbon (AC) and Titania (TiO2) suspension can constitute the emerging technological solution. Objectives: Best lignocellulosic precursor biomass, Melia azedarach (Darek sawdust – DSD), was selected for orthophosphoric acid impregnated AC production and novel AC-DSD-TiO2 nanocomposite was developed. AC-DSD and ACDSD-TiO2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 0 publications
3
2
0
Order By: Relevance
“…These results are contrary to the usual observation that increasing the active sites through increasing the nanocomposite contents should increase nanocomposite efficiency, however, as a heterogeneous photocatalytic reaction depends on the availability of photons, and increasing the nanocomposite dose causes the reaction solution to become turbid, which prevents the photons from reaching the nanocomposite surface and reduces the efficiency of the nanocomposite. Similar findings are reported in previous heterogeneous photocatalytic studies. The rest of the study was conducted using an optimum dose of 1 mg mL –1 .…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…These results are contrary to the usual observation that increasing the active sites through increasing the nanocomposite contents should increase nanocomposite efficiency, however, as a heterogeneous photocatalytic reaction depends on the availability of photons, and increasing the nanocomposite dose causes the reaction solution to become turbid, which prevents the photons from reaching the nanocomposite surface and reduces the efficiency of the nanocomposite. Similar findings are reported in previous heterogeneous photocatalytic studies. The rest of the study was conducted using an optimum dose of 1 mg mL –1 .…”
Section: Resultssupporting
confidence: 83%
“…Similar findings are reported in previous heterogeneous photocatalytic studies. 35 37 The rest of the study was conducted using an optimum dose of 1 mg mL –1 .…”
Section: Resultsmentioning
confidence: 99%
“…The best adapted isotherm models and the adsorption capacity of some different dyes in various TiO 2 /AC adsorbents in aqueous solutions have been investigated by other researchers and these results are summarized in Table 1. The adsorption isotherm study of composites in this research demonstrated similar trends to those reported in the literature [9,[86][87][88]. It also reveals that Fe-TiO 2 /AC or Co-TiO 2 /AC composites could be used as a potential adsorbent for dye removal, despite the decrease of adsorption capacity by increasing the doping percentage, high adsorption capacity values are still obtained in comparison to other studied composites, as displayed in Table 1.…”
Section: Adsorption Isotherms-modelssupporting
confidence: 87%
“…The best adapted isotherm models and the adsorption capacity of some different dyes in various TiO2/AC adsorbents in aqueous solutions have been investigated by other researchers and these results are summarized in Table 1. The adsorption isotherm study of composites in this research demonstrated similar trends to those reported in the literature [9,[86][87][88]. The generated values by the Langmuir model correspond with the plateau of the experimental data observed in Figure 4, and the comparison of R 2 and RMSE between all the models suggests that the Langmuir model was the most suitable model to fit the data.…”
Section: Adsorption Isotherms-modelssupporting
confidence: 86%
“…The textile industry is a major consumer of water, dyes, and other chemicals required in various phases of fabric production. If not properly treated, a significant proportion of effluents including spent or unutilized dyes are likely to be deposited in the freshwater ecosystem (Khan et al., 2020; Shah et al., 2021). Textile dyes are organic substances that are either natural or synthetic and are used to color fabrics.…”
Section: Introductionmentioning
confidence: 99%